Electrical properties and phase transition of Ba(Zr0.05Ti0.95)1 − x(Fe0.5Ta0.5)xO3 ceramics. (September 2015) - Kruea-In, C.; Rujijanagul, G.
Graphical abstract: Highlights: Properties of of Ba(Zr0.05 Ti0.95 )1 −  x (Fe0.5 Ta0.5 ) x O3 ceramics were investigated. Small amount of dopant produced a large change in dielectric and phase transition. A phase diagram of Ba(Zr0.05 Ti0.95 )1 −  x (Fe0.5 Ta0.5 ) x O3 ceramics was proposed. Dielectric tunability increased with increasing x concentration. Abstract: In this work, properties of Ba(Zr0.05 Ti0.95 )1 −  x (Fe0.5 Ta0.5 ) x O3 ceramics with 0.00≤  x  ≤0.07 were investigated. The ceramics were fabricated by a solid state reaction technique. X-ray diffraction analysis indicated that all samples exhibited single phase perovskite. Examination of the dielectric spectra revealed that the Fe and Ta additives promoted a diffuse phase transition, and the two phase transition temperatures, as observed in the dielectric curve of pure Ba(Zr0.05 Ti0.95 )O3, merged into a single phase transition temperature for higher x concentrations. The transformation was confirmed by ferroelectric measurements. In addition, the doped ceramics exhibited high relative dielectric tunability, especially for higher x concentration samples.